Implementation of the CIPP Evaluation Model in the Full Day School Program at Madrasah Aliyah Negeri 1 Soppeng - Syamrina Syamrina; Yuspiani Yuspiani; Mardyawati Mardyawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to see the extent of the evaluation of the full day school program implemented at MAN 1 Soppeng. This study uses a qualitative research design. This study uses a phenomenological approach. The data sources in this study are information from the principal, teachers and staff, students and parents of students who are also informants in this study. The results of the study indicate that the Leadership Curriculum is comprehensively considered good. 1) Viewed from the context aspect, this policy is driven by the need to create a generation that is not only intellectually intelligent, but also excels in spirituality and morality. 2) Viewed from the input aspect, Overall it is adequate. 3) Viewed from the process aspect, that all aspects are key to the successful implementation of the full day school program. 4) and Viewed from the product aspect, the results of the implementation of Full Day School have been able to improve student achievement and are able to balance academics with their spirituality. 5) The main supporting factors lie in the readiness of competent teachers and adequate infrastructure. On the other hand, there are inhibiting factors, such as student boredom due to long learning durations.